Harrison White and Unpleasant Ebullience. - Breigser, Ronald (Connections (02261766), 2025)
I first met Harrison White in 1970, during my initial year of graduate study and his first year as chair of Harvard's newly-reconstituted Department of Sociology. I last visited with him on May 18, 2024, in Tucson, Arizona, the day before he passed away. Harrison has been my north star throughout my career. Our most intensive period in person together was the decade or so beginning in 1971, and that (along with some of Harrison's earlier career) is the timeframe on which I'll focus in these remarks.